2020
DOI: 10.1002/jcla.23434
|View full text |Cite
|
Sign up to set email alerts
|

Detection of submicroscopic chromosomal aberrations by chromosomal microarray analysis for the prenatal diagnosis of central nervous system abnormalities

Abstract: Background Central nervous system (CNS) abnormalities are a group of serious birth defects associated with high rates of stillbirths, infant death, or abnormal development, and various disease‐causing copy number variations play a much more important role in the etiology of CNS abnormalities. This study intends to present a retrospective study of the prenatal diagnosis and the pregnancy outcome of fetuses diagnosed with CNS abnormalities, and evaluate the clinical value of chromosomal microarray analysis (CMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These findings are similar to previous reports, although some of the studies only showed a higher detection rate of non-isolated CNS abnormalities and no significant difference between the two groups. 3,32 In this study, detection of holoprosencephaly (66.7%, 4/6) had the highest positive rate among the different types of CNS abnormalities. All abnormal cases were trisomy 18 syndromes.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…These findings are similar to previous reports, although some of the studies only showed a higher detection rate of non-isolated CNS abnormalities and no significant difference between the two groups. 3,32 In this study, detection of holoprosencephaly (66.7%, 4/6) had the highest positive rate among the different types of CNS abnormalities. All abnormal cases were trisomy 18 syndromes.…”
Section: Discussionmentioning
confidence: 52%
“…These findings are similar to previous reports, although some of the studies only showed a higher detection rate of non-isolated CNS abnormalities and no significant difference between the two groups. 3 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CNS abnormalities are often diagnosed late in pregnancy 10 . When applying conventional methods (karyotyping followed by CMA or CMA alone) to the diagnosis of fetal CNS anomalies, the estimated diagnostic yield does not exceed 20% [11][12][13] . Thus, more than 80% of cases remain without a genetic diagnosis, probably owing to a large proportion of cases having monogenic etiology.…”
Section: Introductionmentioning
confidence: 99%
“…At present, standard genetic diagnostic tools include quantitative fluorescent–polymerase chain reaction for aneuploidy screening and Chromosomal microarray analysis (CMA) for detecting copy number variants. 7 …”
Section: Introductionmentioning
confidence: 99%
“…genetic diagnostic tools include quantitative fluorescent-polymerase chain reaction for aneuploidy screening and Chromosomal microarray analysis (CMA) for detecting copy number variants. 7 Next generation sequencing, such as whole exome sequencing (WES) and whole genome sequencing, is emerging as a valuable tool to diagnose prenatal monogenetic disorders. By sequencing all coding parts of the DNA, WES can detect single nucleotide variants, copy number variants and small deletions or insertions.…”
mentioning
confidence: 99%